Nickel ferrite supported on calcium-stabilized zirconia for solar hydrogen production by two-step thermochemical water splitting. (December 2017) - Reñones, Patricia; Alvarez-Galvan, M. Consuelo; Ruiz-Matas, Laura; Retuerto, Maria; Navarro, Rufino M.; Fierro, Jose Luis G.
Abstract: Solar hydrogen production by thermochemical cycles from water using oxide redox pairs represents a promising technology at medium-long term to storage intermittent solar irradiation. Redox oxides based on nickel ferrite supported on modified zirconia have been prepared and studied for renewable H2 production from water by two-step thermochemical cycles. We report herewith a new material based on nickel ferrite supported on Ca-doped zirconia substrate that presents high efficiency for hydrogen production, which is ascribed to a high active phase dispersion promoted by the inclusion of part of Fe cations in the support lattice and by the formation of calcium zirconate, acting as a physical barrier that hinders sintering. Graphical abstract: Highlights: Excellent performance of NiFe2 O4 supported on Ca-doped ZrO2 sample for H2 production by thermochemical water-splitting. Formation of calcium zirconate which alleviates sintering. Partial incorporation of Fe cations into the support lattice, leading to a high dispersion of the active phase.